Validation of the Arabic version of the Brief Emotional Intelligence Scale - Hallit, Souheil; Obeid, Sahar; Kanj, Gaelle; Malaeb, Diana; Jebreen, Kamel; Azzi, Vanessa; Hallit, Rabih; Fekih-Romdhane, Feten (Frontiers in Psychology, 2026)
BackgroundEmotional Intelligence (EI) has been a widespread topic of scientific research and discussion among individuals and institutions over the last years, giving room for debate concerning its measurement and applications. One of the shortest, simplest, most economical and increasingly used self-report measures is the Brief Emotional Intelligence Scale (BEIS-10), whose validity and reliability have been demonstrated across diverse samples and contexts. The present study examined the psychometric properties of an Arabic translation of the BEIS-10 in a native Arabic-speaking population from Lebanon.MethodsThis cross-sectional study enrolled 449 non-clinical adults (median age = 21 years [min = 18; max = 70]; 70.6% females; median household crowding index = 1 [min = 0.14; max = 8]). The forward-backward translation approach was adopted to develop an Arabic version of the BEIS-10. We used data from the entire sample to perform a Confirmatory Factor Analysis (CFA) using RStudio, “lavaan” and “SemTools” programs. We used the Weighted Least Squares with Mean and Variance (WLSMV) estimation method, which is more appropriate for ordinal data.ResultsCFA indicated that although both the one-factor and five-factor models of the BEIS-10 demonstrated acceptable global fit indices, inspection of the five-factor solution revealed extremely high inter-factor correlations, several approaching unity, indicating poor discriminant validity among the proposed dimensions. Consequently, the unidimensional model of the Arabic BEIS-10 was retained, showing excellent internal consistency as evidenced by McDonald’s ω and Cronbach’s α values of 0.94. The Arabic BEIS-10 showed invariance across gender at the scalar, metric, and configural levels, with no difference between genders in terms of EI. Furthermore, higher EI scores significantly correlated with higher positive and negative affect, thus attesting to the concurrent validity of the Arabic BEIS-10.ConclusionFindings suggest that the Arabic BEIS-10 is a valid and reliable self-report measure for the assessment of EI in Arab settings. Considering its simple and brief administration, this version of the scale might be of better convenience in Arab settings beset by shortage of resources and financial turmoil. It also has practical implications as it enables research on EI in diverse cultural contexts, and enhances educational and workplace programs by tailoring emotional intelligence training to local needs.